BITUMEN CONCENTRATION FROM ASBUTON SETTLING METHOD IN HOT WATER MEDIUM - Zezar Ahmad, M.
itumen is a thermoplastic material that is solid at room temperature and will melt when heated and solidify again when the temperature is lowered without changing its physical and chemical properties. Asphalt is a mixture of pavement forming material. Asbuton is a type of natural asphalt obtained from Buton Island, Southeast Sulawesi, having impurity minerals, generally in the form of calcium carbonate (CaCO3) and several other minerals which are an estimated total of 70% wt – 85% wt. Asbuton reserves are 677 million tons or equivalent to 170 million tons of oil asphalt and can replace the use of petroleum asphalt (refinery from petroleum). The deposition process in hot water medium is one of the bitumen concentration of impurities. The process of concentration of hot water is combined with a solvent that enhances settling process. Because it has a CaCO3 impurities that have much higher solubility of the impurities of silica (SiO2) in water, so it must be combined with the addition of a surfactant. To prevent bitumen and its impurities from mixing again, a sealing agent is used. The previous research bitumen concentration asbuton has not obtained optimal recovery due to improper use of solvents and surfactants. To obtain a higher recovery used kerosene solvent, surfactant alkyl benzene sulfonate (ABS) and sodium carbonate (Na2CO3) are used as a sealing agent. Research carried out by settling method in a medium hot water to the sample size distribution of -35 mesh. In the first experiment using various temperature of 65oC, 75oC, 85oC, 95oC and using various solvent of 30%, 40%, 50%, 60%. In the second experiment using a variation of the surfactant variable 2%, 4%, 6%, and 8% also using various of 50% and 60% solvent variable. Settling process performed for 75 hours in hot medium 100oC. Characterization was carried out using X-ray diffraction (XRD), X-ray fluroresence (XRF), scanning electron microscopy dispersive X-ray Spectroscopy (SEM-EDS) dan fourier transform infrared (FTIR), contact angle and analysis of asbuton sample grade using socklet. The experimental results show that the higher the temperature, solvent and surfactant, the higher the percent recovery is obtained. The maximum recovery from the effect of adding temperature and kerosene was obtained at the temperature of 95oC and addition of percent to kerosine accounted for 60% which resulted in 96% recovery, carried out at the addition of 2% surfactant. The maximum recovery from the effect addition of percent surfactant was obtained at the addition of 8% surfactant and 60% addition to kerosene which resulted in 94% recovery, carried out at the temperature of 85oC.